Investigating the impact of tocilizumab on serum cytokines concentrations in Japanese FMF patients: a sub-analysis of the NUH01FMF study - Tomohiro Koga; Shuntaro Sato; Kaori Furukawa; Hiroshi Yamamoto; Atsushi Kawakami (Immunological Medicine)
Familial Mediterranean Fever (FMF) is the most common hereditary autoinflammatory disease, characterized by recurrent fever, arthritis, rash, and serositis, and is caused by mutations in the MEFV gene coding for the pyrin protein. The primary treatment goal is to prevent acute attacks and minimize subclinical inflammation to avoid secondary amyloidosis with colchicine as the first-line treatment. However, 10-20% of patients are colchicine-resistant or intolerant. While the therapeutic potential of IL-6 inhibitors such as tocilizumab (TCZ) has been suggested, the detailed serum cytokine profiles after TCZ treatment in patients with FMF remain largely unexplored. This study focused on a sub-analysis of a clinical trial evaluating TCZ in patients with colchicine-resistant FMF (crFMF). We analyzed the serum cytokine profiles at 0, 2, 4, 8, 12, 16, 20, and 24 weeks in the TCZ and placebo groups. Our findings revealed a decrease in serum C-X-C motif chemokine ligand 1 and vascular endothelial growth factor levels in the TCZ group at week 4 compared to baseline, which persisted until week 24, indicating the potential of TCZ to manage crFMF by modulating specific inflammatory cytokines. Further research is required to confirm these findings and optimize the treatment strategies for FMF.